Prevalence of exposure to secondhand smoke among higher secondary school students in Ernakulam District, Kerala, Southern India - P S Rakesh; Jishnu Satheesh Lalu; K Leelamoni (Wolters Kluwer Medknow Publications, 2017)
Introduction: The association between secondhand smoke and health outcomes, such as frequent respiratory infections, ischemic heart disease, lung cancer, asthma, and stroke, has long been established. The study aimed to estimate the prevalence of secondhand smoking exposure among higher secondary school students in Ernakulam district, Kerala, Southern India. Materials and Methods: A structured questionnaire was administered to all students from four randomly selected higher secondary schools in Ernakulam district. Descriptive statistics was done using frequencies and percentages. Univariate and multivariate analyses were done for factors associated with household exposure to tobacco smoke generating odds ratios (ORs) and 95% confidence intervals (CIs). Results: A total of 629 students participated in the study. The prevalence of ever smokers was 11.9% and of current smokers was 5.2%. Among the study participants, 23.2% were exposed to secondhand smoking from a family member and 18.8% from friends. Lower educational status of father was associated with the household exposure to secondhand smoke (adjusted OR 4.51 [95% CI 1.66-12.22]). More than half of the study participants (56.3%) reported that they were exposed to cigarette smoke in past 1 week in a public place and 10.2% in closed public places. Nearly one-third of the students reported that they have seen somebody smoking inside school campus in the past 30 days. Conclusion: Exposure to secondhand smoke at home, schools, and public places was higher among the late adolescent higher secondary school students in Ernakulam district. The findings underscore the urgent need for increased efforts to implement the strategies to reduce secondhand smoke exposure among adolescents.